1995
DOI: 10.2134/agronj1995.00021962008700050038x
|View full text |Cite
|
Sign up to set email alerts
|

Wheat Response to Row Spacing in Relay Intercropping Systems

Abstract: Relay intercropping of soybean [Glycine max (L.) Merr.] or cotton [Gossypium hirsutum L.] into standing wheat [Triticum aestivum L.] allows for earlier planting of the summer crop than with sequential double‐crop systems. Relay intercropping has been evaluated using modifications of standard planting and harvesting equipment as well as specifically designed equipment. In most relay intercropping systems, wheat is drilled in the fall in a row pattern that provides traffic‐tire lanes as guides for planting the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
28
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 2 publications
0
28
1
Order By: Relevance
“…However, deep tillage has a few issues such as requiring large tractors with significant horsepower to pull each shank (14-20 Kw), consumption of copious amounts of fuel (20-25 L ha À1 ; Karlen et al, 1991), and deep tillage is usually needed annually to prevent re-setting of the dense soil layer (Threadgill, 1982;Porter and Khalilian, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…However, deep tillage has a few issues such as requiring large tractors with significant horsepower to pull each shank (14-20 Kw), consumption of copious amounts of fuel (20-25 L ha À1 ; Karlen et al, 1991), and deep tillage is usually needed annually to prevent re-setting of the dense soil layer (Threadgill, 1982;Porter and Khalilian, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…For these soils, management involves noninversion tillage 0.3-0.4 m deep to disrupt the hard layer. Though residual effects of tillage can remain for years afterward as seen by Munkholm et al (2001) and Baumhardt and Jones (2002), tillage is still performed annually on these southeastern USA Coastal Plain soils because annual re-compaction can reduce root growth and yield even though it is not complete (Porter and Khalilian, 1995). A recent study (Frederick et al, 1998) showed that deep tillage significantly increased yield when it was performed twice a year, before double-cropped wheat and drilled soybean.…”
Section: Introductionmentioning
confidence: 99%
“…Deep tillage of these coastal soils is recommended annually (Porter and Khalilian 1995;Simoes et al 2009) to reduce soil strength and promote root growth throughout the profile to encourage water and nutrient uptake. In some studies, residual effects of deep tillage were shown to be effective for years (Munkholm, Schjønning, and Rasmussen 2001;Scanlon et al 2009), especially if traffic is limited to specific midrows (Frederick et al 1998), whereas in other studies tillage effects were gone after 3 years or less (Busscher et al 1995;Shukla, Lal, and Ebinger 2003).…”
Section: Introductionmentioning
confidence: 99%